2013
DOI: 10.1634/theoncologist.2013-0039
|View full text |Cite
|
Sign up to set email alerts
|

Differential Chemotherapeutic Sensitivity for Breast Tumors With “BRCAness”: A Review

Abstract: BRCA1 or BRCA2 mutations predispose to cancer development, primarily through their loss of role in the repair of DNA double-strand breaks. They play a key role in homologous recombination repair, which is a conservative, error-free DNA repair mechanism. When mutated, other alternative, errorprone mechanisms for DNA repair take over, leading to genomic instability. Somatic mutations are rare in sporadic breast tumors, but expression of BRCA1 and BRCA2 genes can be downregulated in other mechanistic ways. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 53 publications
1
47
0
1
Order By: Relevance
“…BRCAness is defined as patients without BRCA mutations, but with epigenetic inactivation of BRCA, mutations in other genes, or post-translational modifications of key proteins involved in HR and pharmacological inhibitors of the HR, resulting in impairment of HR. 18,19 The BRCAness is identified in at least 25% of BRCA wild-type breast cancers and is more frequent in TNBC. 20,21 The BRCA1 promoter CpG island methylation is in approximately 30% of TNBC patients 22 and tumors with this methylation share the pattern of gene expression similar to inherited BRCA1-mutated breast cancers.…”
Section: Molecular Mechanisms Of Platinum and Homologous Recombinatiomentioning
confidence: 99%
“…BRCAness is defined as patients without BRCA mutations, but with epigenetic inactivation of BRCA, mutations in other genes, or post-translational modifications of key proteins involved in HR and pharmacological inhibitors of the HR, resulting in impairment of HR. 18,19 The BRCAness is identified in at least 25% of BRCA wild-type breast cancers and is more frequent in TNBC. 20,21 The BRCA1 promoter CpG island methylation is in approximately 30% of TNBC patients 22 and tumors with this methylation share the pattern of gene expression similar to inherited BRCA1-mutated breast cancers.…”
Section: Molecular Mechanisms Of Platinum and Homologous Recombinatiomentioning
confidence: 99%
“…Previous reports have also demonstrated that the sporadic TNBC cells exhibiting similar DNA repair defects, i.e., BRCAness, are also sensitive to PARP inhibitors, cisplatin and other DNA-damaging chemotherapy [2, 19, 20]. Here, BRCAness may be caused by DNA methylation and depletion of BRCA1 expression [21], or due to mutation or depletion of other proteins involved in HR [22]. Based on this, clinical trials of PARP inhibitor in TNBC, including olaparib and veliparib, are ongoing [23].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, because BRCAMut tumors cannot repair DSBs induced by agents such as bifunctional alkylators and platinum salts, they are hypersensitive to DSB-inducing agents and probably to PARP inhibitors. [11][12][13][14] Assessment of BRCAness using array comparative genomic hybridization (aCGH) or multiplex ligation-dependent probe amplification (MLPA) has recently been described. 15 Patients with BRCAness tumors survive longer when treated intensively with alkylating agents as adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%